Accelerated catalytic ozonation for aqueous nitrobenzene degradation over Ce-loaded silicas: Active sites and pathways - Wang, Qinghong; Ji, Yuanyuan; Hu, Jingze; Ye, Huangfan; Liu, Ya; Wang, Yuxian; Chen, Chunmao; Li, Zhuoyu (Frontiers in Environmental Science, 2022)
Cerium oxides loaded silica catalysts were synthesized by an impregnation method by simply mixing Ce precursor with silica spherule (Ce/SS) and ordered MCM-41 zeolites (Ce/MCM-41), followed by a mild calcination. Compared with pure SS and MCM-41, Ce modified Ce/SS and Ce/MCM-41 demonstrate much improved catalytic ozonation activities for mineralization of recalcitrant nitrobenzene (NB). At solution pH of 6, 86% and 97% TOC mineralization rates were achieved within 60 min for Ce/MCM-41 and Ce/SS, respectively. Characterization results suggest that Ce loading significantly increases the surface Lewis acidic sites, which would synergize with Ce3+/Ce4+ redox cycle for the activity improvement. With the aid of in situ electron paramagnetic resonance (EPR) spectra and quenching tests, hydroxyl radical (·OH), superoxide radical (O2•–), and singlet oxygen (1O2) are identified as the O3 catalytic decomposition products, while ·OH mainly accounts for NB mineralization. The detailed degradation route of NB was further investigated by the multi-chromatography analysis. NB is firstly oxidized into polyhydroxy compounds, followed by small molecular organic acids, and finally being mineralized into CO2 and H2O. This study established a facile strategy to synthesize highly active and stable Ce/SiO2 catalysts for catalytic ozonation, and elucidated the in-depth mechanisms for the activity origins of the Ce loaded silica-based materials in catalytic ozonation processes (COP).